The Long-Run Performance of Initial Public Offerings. - Ritter, Jay R (Journal of Finance, 1991)
The underpricing of initial public offerings that has been widely documented appears to be a short-run phenomenon. Issuing firms during 1975-84 substantially underperformed a sample of matching firms from the closing price on the first day of public trading to their three-year anniversaries. There is substantial variation in the under performance year-to-year and across industries, with companies that went public in high-volume years fairing the worst. The patterns are consistent with an initial public offering market in which (1) investors are periodically overoptimistic about the earnings potential of young growth companies, and (2) firms take advantage of these "windows of opportunity."